2015
DOI: 10.1590/1984-70332015v15n3a26
|View full text |Cite
|
Sign up to set email alerts
|

Genetic base of Brazilian irrigated rice cultivars

Abstract: - (1965-1980, 1981-1990, 1991-2000 and 2001-2012). For each grouping, the previously described factors were also estimated. A total of 110 cultivars were studied and it was concluded that the genetic base of Brazilian irrigated rice cultivars is narrow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…However, this will only be possible as long as genetic variability is maintained. In Brazilian irrigated rice breeding programs, genotypic variability is restricted (Rabelo, Guimarães, Pinheiro, & Silva, 2015;Streck, Aguiar, Magalhães Júnior, Facchinello, & Oliveira, 2017); therefore, investigating the genetic diversity of rice genotypes is critical.…”
Section: Introductionmentioning
confidence: 99%
“…However, this will only be possible as long as genetic variability is maintained. In Brazilian irrigated rice breeding programs, genotypic variability is restricted (Rabelo, Guimarães, Pinheiro, & Silva, 2015;Streck, Aguiar, Magalhães Júnior, Facchinello, & Oliveira, 2017); therefore, investigating the genetic diversity of rice genotypes is critical.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this release does not follow mentioned by Rabelo et al (2015) who found that the irrigated rice Brazilian cultivars have narrow genetic base. This result can be explained mainly by the intrinsic characteristics regarding the type of grain and plant architecture, the BRS AG neither has grains of the indica subspecies type nor modern-Philippine architecture.…”
Section: Performance Characteristicsmentioning
confidence: 68%
“…Similar evidence was described by Reig-Valiente et al (2016), who showed that breeding for a specific region even tends to genetically isolate the germplasm regarding adaptability. The second reason is probably more important, as studies have named the causes for the narrowing of the genetic base of rice by genealogy records, showing that few ancestors represent the base of practically all breeding programs, and that in addition, over decades, few parents were used repeatedly in crosses, affecting the resulting variability (Rangel et al 1996, Raimondi et al 2014, Rabelo et al 2015. Regarding the datasets used in this study, it is possible to assume that the results of SNP markers are the most refined.…”
Section: Resultsmentioning
confidence: 99%
“…more than 80% of all Brazilian rice (SOSBAI 2018). In fact, studies have reported evidence for the gradual narrowing of the genetic variability among the elite cultivars grown in southern Brazil (Rangel et al 1996, Raimondi et al 2014, Rabelo et al 2015, Streck et al 2018, Streck et al 2019. However, it is important to emphasize that these studies may have applied datasets and methods with somehow restricted efficiency to evaluate the genetic variability.…”
Section: Introductionmentioning
confidence: 99%